The Potential of State Languages of the Subjects of the Russian Federation in the Procedural Branches of Law Using the Example of Civil Proceedings - Valeev, D.Kh; Nuriev, A.G.; Shakiryanov, R.V. (Uchenye zapiski Kazanskogo universiteta. Serii͡a︡ Gumanitarnye nauki, 2019)
The use of the state languages of the subjects of the Russian Federation in various areas of public relations is conditioned by the federal structure of the state and favors the development of these languages. At the same time, despite the availability of constitutionally guaranteed provisions, many gaps still occur in the use of the state languages of the constituent entities of the Russian Federation in legal proceedings. For example, the system of existing legal regulators fails to apply a unified approach to the implementation of the constitutional right to judicial protection in the state languages of the constituent entities of the Russian Federation. Two aspects have been distinguished in the implementation of these guarantees within the procedural branches of law: firstly, hearing a civil case in the state language of a constituent entity of the Russian Federation and, secondly, hearing a case in the Russian language with the assistance of an interpreter. The problems associated with the ability to make service documents and court decisions in the state language of the subject of the Russian Federation have been defined. Special attention has been paid to the status, role, and procedural functions of an interpreter in civil proceedings.